Solution structure of the transmembrane domain of the mouse erythropoietin receptor in detergent micelles - Li, Qingxin (Sci Rep, 2015)
Erythropoiesis is regulated by the erythropoietin receptor (EpoR) binding to its ligand. The transmembrane domain (TMD) and the juxtamembrane (JM) regions of the EpoR are important for signal transduction across the cell membrane. We report a solution NMR study of the mouse erythropoietin receptor (mEpoR) comprising the TMD and the JM regions reconstituted in dodecylphosphocholine (DPC) micelles. The TMD and the C-terminal JM region of the mEpoR are mainly α-helical, adopting a similar structure to those of the human EpoR. Residues from S216 to T219 in mEpoR form a short helix. Relaxation study demonstrates that the TMD of the mEpoR is rigid whilst the N-terminal region preceding the TMD is flexible. Fluorescence spectroscopy and sequence analysis indicate that the C-terminal JM region is exposed to the solvent. Helix wheel result shows that there is hydrophilic patch in the TMD of the mEpoR formed by residues S231, S238 and T242, and these residues might be important for the receptor dimerization.